Clima laboral en el departamento de ventas de Bell Novainser S. A. del cantón Babahoyo. - Freire Acosta, Leydi Katiuska (2022)
The work environment within organizations is of great importance since it allows them to have a pleasant space and environment, since it influences comfort within the work space, if there is a harmonious work environment it will allow workers to increase productivity , profitability and meeting the objectives established by the company and if there is not a good working environment, it affects labor relations and the performance of workers; Therefore, the objective of this work was to analyze the causes that affect the work environment in the sales department of Bell Novainser S.A. of the Babahoyo canton, from the systematization of the theoretical foundation taking as a reference the work environment within the organizations and the problems that are found in the area to be analyzed within the company, obtaining results through the applied techniques that were the interview to the boss and the survey. applied to vendors. In the conclusions it has been determined that in the sales department of this company there are several shortcomings that have affected the work environment, interfering in communication between employees and affecting labor relations, making it difficult to meet the company's goals.